Regulation of transport properties by polytypism: a computational study on bilayer MoS2 - Banerjee, Swastika; Park, Jaehong; Hwang, Cheol Seong; Choi, Jung-Hae; Lee, Seung-Cheol; Pati, Swapan K. (ROYAL SOC CHEMISTRY, 2017)
Being a member of the van der Waals class of solids, bilayer MoS2 exhibits polytypism due to different possible stacking arrangements, namely, 2H(c), 2H(a) and 3R-polytypes. Unlike monolayer MoS2, these bilayers exhibit indirect band gaps. Band extrema states originate from a linear combination of Mo-(d) and S-(p) orbitals which are sensitive to the interlayer interactions. We have studied the impact of stacking pattern on the electronic structure and electron/hole transport properties of these polytypes. Based on first-principles computations coupled with the Boltzmann transport formalism, we found that a strong electron-hole anisotropy can be realised in the 2H(a)-MoS2 polytype unlike in a monolayer which is isotropic in nature. A staggered arrangement between two layers results in a higher relaxation time for electrons compared to holes leading to anisotropy which is of importance in device engineering.
Keywords: ELECTRONIC-STRUCTURE; TRANSISTORS; TRANSITION; ANISOTROPY; MOBILITY; HOLE